(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To investigate gender differences in factors related to lifestyle habits among elderly outpatients receiving treatment at the Endocrinology Clinic of Thong Nhat Hospital. Subjects and Methods: A cross-sectional study was conducted on patients aged ≥ 60 years who attended the Endocrinology Clinic of Thong Nhat Hospital from October 2025 to December 2025. Results: The study included 270 elderly patients with diabetes mellitus, with a mean age of 70.3 ± 7 years; males predominated, accounting for 62.59%. The two most common comorbidities were hypertension (89.3%) and dyslipidemia (92.6%). The prevalence of regular physical exercise was higher in men (58.6%) than in women (43.6%). However, unhealthy lifestyle behaviors such as alcohol consumption and cigarette smoking were also more prevalent among men than women. Multivariable logistic regression analysis identified sex as a factor strongly associated with physical activity, alcohol consumption, and smoking habits. In addition, age was found to be associated with physical activity among elderly patients with diabetes mellitus. Conclusion: The study demonstrates that lifestyle behaviors among elderly patients with diabetes mellitus are closely associated with sex and age. Men exhibit higher levels of physical activity but also show a higher prevalence of unhealthy behaviors such as alcohol consumption and tobacco use; meanwhile, increasing age tends to be associated with reduced levels of physical activity.